ANALISIS TINGKAT KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN (PBB) DI DESA SUNGAI KERANJI KABUPATEN KUANTAN SINGINGI - Yeni Sapridawati; Rina Andriani; Diskhamarzaweny Diskhamarzaweny; Yul Emri Yulis; M. Irwan (Jurnal Akuntansi Kompetif, 2026)
This study aims to determine the level of taxpayer compliance and the factors influencing taxpayers in paying Land and Building Tax (PBB) in Sungai Keranji Village, Kuantan Singingi Regency. This research is a descriptive study that attempts to describe the actual situation. Data collection techniques used by the researcher were interviews, observations, and documentation studies. The results of this study indicate that the level of compliance with Land and Building Tax (PBB) in Sungai Keranji Village from 2022-2023 has increased, while in 2024 the level of compliance with Land and Building Tax has decreased. Factors that cause community compliance with PBB payments are: 1. The level of taxpayer awareness in Sungai Keranji Village is quite high regarding PBB payments, 2. The level of education of the Sungai Keranji Village community is quite good, 3. Due to the economic conditions of the Sungai Keranji Village community is quite good so that the community is willing to set aside funds for payments for land and buildings that they have controlled and they use and 4. Sanctions in the form of fines have a significant impact on the level of Land and Building Tax revenue each year in Sungai Keranji Village Keywords: Compliance Level, Tax Payers, Land and Building Tax